2021
DOI: 10.1108/ijhma-08-2021-0096
|View full text |Cite
|
Sign up to set email alerts
|

Gulf property damage, housing price trends and US bankruptcy filings

Abstract: Purpose This paper aims to examine potential causes of bankruptcy as they relate to hurricane damage. Investigate whether hurricanes result in personal bankruptcy filings due to real property damages. Strengthen existing descriptive results by using fully modified ordinary least squares (FMOLS). Design/methodology/approach Lagged FMOLS model is used with data from states that suffered hurricane damage between 2000 through 2020. FMOLS controls for various financial distresses that can cause bankruptcy filings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Of more recent studies, Brotman and Katzman (2021) examined five states bordering the Gulf of Mexico. They found that the divorce rate was an insignificant variable when explaining bankruptcy filing rates.…”
Section: Literature Searchmentioning
confidence: 99%
“…Of more recent studies, Brotman and Katzman (2021) examined five states bordering the Gulf of Mexico. They found that the divorce rate was an insignificant variable when explaining bankruptcy filing rates.…”
Section: Literature Searchmentioning
confidence: 99%